Um estalo nas faculdades de direito: perspectivas ideológicas da Assessoria Jurídica Universitária Popular. - Almeida, Ana Lia Vanderlei de (2015)
The thesis titled "A snap in law schools: ideological perspectives of university students’ popular legal counsels" has as analysis object the University Students' Popular Legal Counsel (AJUP), consisting of a particular student movement linked to law schools. Within the subject of legal education and starting from the ideology category , the research raises questions about the type of counterpoint that AJUP holds in law, seeking to be on the side of workers and other subaltern subjects in class society. Having the conception of dialectical historical materialism as a methodological starting point, I’ve developed a field research that counted with the participative observation and the conduction of semi-structured interviews with groups of university students’ popular legal counsels. The field of the research comprehended eight member groups of the National Network of University Legal Counsel (RENAJU), linked to federal universities located at the state capitals of the Northeast region of Brazil. The goal of the research is to problematize the possibilities, the contradictions and the limits of AJUP as an ideological perspective of confrontation in the juridical complex. Hence, in the first chapter I sought to outline the notion of ideology use inside the Marxist tradition, as a practical consciousness of the class society, according to István Mészáros (2004), and to characterize how AJUP has adapted to a wider context of political-social mobilization since the resumption of democracy, with the end of the civil-military dictatorship in Brazil. In the second chapter, I’ve characterized the dominant perspective in law and problematized its relationship with AJUP. Finally, I have analyzed four central aspects of the practice in question, popular education, horizontality, the student protagonism and affectionality. The theoretical benchmark is located at the Marxist tradition, having I. Mészáros as a main reference for discussion of ideology, but also K. Marx and G. Lukácx; and, for the discussion about law, K. Marx, F. Engels, K. Kautsky, E. Pachukanis and G. Lukács. I also sought the interlocution with some analysis pointed at the Brazilian reality, sometimes closer, sometimes farther from Marxism, to comprehend the peculiarities of the liberal ideology in Brazil and also the question of popular education. I conclude that the ideological perspectives of AJUP present contradictions and limitations closely related to the current context of the left-wing movements, and they are also implicated in the broad spectrum of the juridical fetishism, without which the roles played by law in the reproduction of the capitalist society couldn’t be played. The possibilities offered by the ideological confrontations played by AJUP are related to the possibilities of resumption of a project associated to the workers and other subordinate subjects in the class society capable of going beyond the capital.